Nephrogenic syndrome of inappropriate antidiuresis secondary to an activating mutation in the arginine vasopressin receptor AVPR2. (4th February 2016) - Powlson, Andrew S.; Challis, Benjamin G.; Halsall, David J.; Schoenmakers, Erik; Gurnell, Mark
Summary: Context: Nephrogenic syndrome of inappropriate antidiuresis (NSIAD), resulting from activating mutations in the arginine vasopressin receptor type 2 (AVPR2), is a rare cause of hyponatraemia. However, its true prevalence may be underestimated and it should be considered in the investigation of unexplained hyponatraemia, with implications for management and targeted gene testing. Objective: We describe a structured approach to the investigation of hyponatraemia in a young patient, which allowed a diagnosis of NSIAD to be made. We review current knowledge of NSIAD and use a structural modelling approach to further our understanding of the potential mechanisms by which the causative mutation leads to a constitutively active AVPR2. Design: Clinical and biochemical investigation of hyponatraemia; a formal water load test with measurement of arginine vasopressin levels (AVP); sequencing of AVPR2; and computed structural modelling of the wild‐type and constitutively activated mutant receptors. Results: A 38‐year‐old man presented with intermittent confusion and nausea associated with hyponatraemia and a biochemical picture consistent with syndrome of inappropriate antidiuretic hormone (SIADH). Adrenocortical and thyroid function and an acute intermittent porphyria screen were normal. Cross‐sectional imaging of the head, chest and abdomen did not identify an underlying cause and so we proceeded to a water load test. This demonstrated a marked inability to excrete a free water load (just 15% of a 20 ml/kg oral load by 240 min postingestion), with the onset of hyponatraemia (Na + 125 mmol/l, urine osmolality 808 mOsm/kg). However, AVP levels were low throughout the test (0·4–0·9 pmol/l), consistent with a diagnosis of NSIAD. AVPR2 sequencing revealed a previously described hemizygous activating mutation (p.Arg137Cys). Through structural modelling of AVPR2, we suggest that disruption of a hydrogen bond between residues Thr269 and Arg137 may promote stabilization of the receptor in its active conformation. Since diagnosis, the patient has adhered to modest fluid restriction and remained well, with no further episodes of hyponatraemia. Conclusion: NSIAD should be considered in young patients with unexplained hyponatraemia. A water load test with AVP measurement is a potentially informative investigation, while AVPR2 sequencing provides a definitive molecular genetic diagnosis and a rationale for long‐term fluid restriction.